VRK1 Depletion Facilitates the Synthetic Lethality of Temozolomide and Olaparib in Glioblastoma Cells - Navarro-Carrasco, Elena; Lazo, Pedro A. (Frontiers in Cell and Developmental Biology, 2021)
Background: Glioblastomas treated with temozolomide frequently develop resistance to pharmacological treatments. Therefore, there is a need to find alternative drug targets to reduce treatment resistance based on tumor dependencies. A possibility is to target simultaneously two proteins from different DNA-damage repair pathways to facilitate tumor cell death. Therefore, we tested whether targeting the human chromatin kinase VRK1 by RNA interference can identify this protein as a novel molecular target to reduce the dependence on temozolomide in combination with olaparib, based on synthetic lethality. Methods: Depletion of VRK1, an enzyme that regulates chromatin dynamic reorganization and facilitates resistance to DNA damage, was performed in glioblastoma cells treated with temozolomide, an alkylating agent used for GB treatment; and olaparib, an inhibitor of PARP-1, used as sensitizer. Two genetically different human glioblastoma cell lines, LN-18 and LN-229, were used for these experiments. The effect on the DNA-damage response was followed by determination of sequential steps in this process: H4K16ac, γH2AX, H4K20me2 and 53BP1. Results: The combination of temozolomide and olaparib increased DNA damage detected by labeling free DNA ends, and chromatin relaxation detected by H4K16ac. The combination of both drugs, at lower doses, resulted in an increase in the DNA damage response detected by the formation of γH2AX and 53BP1 foci. VRK1 depletion did not prevent the generation of DNA damage in TUNEL assays, but significantly impaired the DNA damage response induced by temozolomide and olaparib, and mediated by γH2AX, H4K20me2 and 53BP1. The combination of these drugs in VRK1 depleted cells resulted in an increase of glioblastoma cell death detected by annexin V and the processing of PARP-1 and caspase-3. Conclusion: Depletion of the chromatin kinase VRK1 promotes tumor cell death at lower doses of a combination of temozolomide and olaparib treatments, and can be novel alternative target for therapies based on synthetic lethality.